THE EFFECT OF ALLOWANCE, PEER ENVIRONMENT, AND INFORMATION AND TECHNOLOGY ACCESS ON ONLINE GAMBLING DECISIONS AMONG UNIVERSITY STUDENTS IN DENPASAR CITY - Patricia Clarisa Dellastrada; I Made Endra Kartika Yudha (CV. Adiba Aisha Amira, 2025)
The presence of the internet has had a tremendous impact on humans. One consequence of the rapid development of technology is increased access to various digital platforms, including the increasingly worrying phenomenon of online gambling. This phenomenon is expected to become more widespread among university students, particularly in Denpasar City. Students in this region face complex life dynamics, influenced by economic, social, and technological advances. Pocket money, as an economic aspect, plays a crucial role in supporting academic and non-academic activities, while the peer environment also shapes behavioral patterns and decision-making. On the other hand, access to information and technology presents both opportunities and challenges for students in their daily learning and social interactions. This study aims to analyze the influence of pocket money, peer environment, and access to information and technology on university students in Denpasar City. The study used a quantitative approach with a survey method by distributing questionnaires to 100 students from various universities in Denpasar City. The data analysis technique used was multiple linear regression to test the influence of each independent variable. The results showed that, simultaneously and partially, the variables of pocket money, peer environment, and access to information and technology had a positive and significant influence on online gambling decisions among university students in Denpasar City. These findings confirm that economic, social, and technological factors are the main determinants in shaping the behavior and life patterns of students in the digital era.